Impact of omitting annual reviews for COPD on patient reported care quality– outcomes from the Asthma+Lung COPD patient passport - Anthony A Laverty; Andrew Cumella; Nicholas S Hopkinson; Keir Elmslie James Philip; MIKE POLKEY; Parris Jade Williams; Leena Bachir (BMJ Open, 2024)
Background Regular clinical reviews of people with COPD provide an opportunity to optimise management and are recommended in national and international guidelines. However, there are limited data about the relationship between having an annual review and other aspects of care quality, which might influence decision-making by healthcare professionals and commissioners.Method Using data from 74 827 people with COPD completing the Asthma+Lung UK COPD Patient Passport, between 2014 and 2022, we conducted adjusted logistic regression (adjusting for year) and compared receipt of key items of care between those reporting that they had had an annual review (65.3%) and those who did not (34.7%). To further capture patient experience, we also analysed 4228 free-text responses to the 2021 Asthma+Lung UK annual COPD survey to the question ‘What is the one thing that could improve your COPD care?’Results We found that the absence of an annual review was associated with significantly worse COPD care across all domains studied; in particular, inhaler training (yes: 80.8% vs no: 38.4%, adjusted OR (AOR): 8.18, 95% CI (7.89 to 8.47), having a written care plan (89.6% vs 56.9%, AOR 6.68 (95% CI 6.35 to 7.05) and medication knowledge (72.6% vs 33.6%, AOR 5.73 (95% CI 5.51 to 5.96). Thematic analysis of the 2021 COPD survey responses identified three areas to improve care: (1) access and support from healthcare services, (2) improved treatment effectiveness and (3) interaction between COPD and the social environment.Discussion Failure to deliver annual COPD reviews is associated with worse patient-reported experience of care quality. In parallel, people with COPD express a desire for greater support and access to healthcare services.